Potensi Ekstrak Etanol Herba Apu-Apu (Pistia stratiotes) dan Fraksi-Fraksinya Sebagai Antioksidan Dengan Metode DPPH - Dewi Dianasari; Irawati Firdiyansari (Pharmacon: Jurnal Farmasi Indonesia, 2019)
Free radicals play an important role in cell damage and degenerative diseases such as coronary heart disease, stroke, premature aging and others. Compounds that can inhibit free radicals are antioxidants. One of the plants that has a high phenolic compound and can be a source of natural antioxidants, apu-apu or Pistia stratiotes. This research was conducted to scientifically prove the antioxidant activity of the apu-apu herbal extract (Pistia stratiotes) and its fractions by the DPPH method. The sample used in the form of all parts apu-apu (apu-apu herb) obtained from the Sumbersari District, Jember Regency. In this study the DPPH method was used with a DPPH concentration of 0.1 mM, incubation time of ethanol extract 40 minutes, fraction of n-hexane 50 minutes, ethyl acetate fraction 45 minutes, ethanol-water fraction 40 minutes,vitamin C 35 minutes and measured at wavelength 517 nm . The results of the average antioxidant activity (IC50) were apu-apu herbal extract 16.675 µg / mL ± 0.239, n-hexane fraction 29.915 µg / mL ± 0.156, ethyl acetate fraction 11.875 µg / mL ± 0.038, ethanol-water fraction 9.090 µg / mL ± 0.156, ethyl acetate fraction 11.875 µg / mL ± 0.038, ethanol-water fraction 9.090 µg / mL ± 0.156, ethyl acetate fraction 11.875 µg / mL ± 0.038 / mL ± 0.122, and vitamin C 3.263 µg / mL ± 0.032. Vitamin C as a positive control had the highest activity, whereas the apu-apu sample which had the highest antioxidant activity was the ethanol-water fraction, and the lowest was the n-hexane fraction. The conclusion of this study is apu-apu herbal ethanol extract and its fractions have antioxidant activity, from high to low sequentially: ethanol-water fraction, ethyl acetate fraction, apu-apu herbaceous fraction, n- fraction hexane.